Cardenales en miniatura: la imagen del poder a través del clero capitular cordobés - Díaz Rodríguez, Antonio J. (2013)
House and chapel were suitable instruments for the transmission of an image of power and privilege to the rest of the Castilian society in the Modern Age. The members of the capitular clergy played a key role in this sense within the strategies of promotion and emulation of their families, and that is what this article tries to show through the example of the Cathedral Chapter of Cordoba